A Free Man - Sethi, Aman, 1983- (India Random House, 2012)
Depicts the lives of a group of homeless friends living in the Old Delhi Railway Station in India and the adventures and misfortunes they experienced that ultimately brought each of them there.
Keywords: India--Delhi -- Social conditions -- Marginality, Social